MILK QUALITY PROFILE OF ETAWAH GOATS REARED BY SMALLHOLDER FARMERS IN BUSUNGBIU DISTRICT, BULELENG REGENCY, BALI PROVINCE - H. P. S., Yosafat; Oka, A. A.; Doloksaribu, L. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
This study was undertaken to establish a database identifying constraints to, challenges of and opportunities for rearing goats in Bali Province.  Data was collected through direct observations, structured formal household interviews, key informant interviews, focus group discussions, and case studies, from the surrounding environment and market assessments from July to September 2018.  A survey was conducted on three goat farmers integrated with Coffea spp., and Theobroma cacao in Buleleng Regency.  All three farmers fed roughage about 5 kg/head/day (TrC) to lactating does, one farmer added 10% of the roughage with Pennisetum purpureum cv. Mott silage (TrO) and another farmer added an ad lib mixture of probiotic with drinking water (TrP). Data of milk profile of 10 lactating does that had average body weight 32.9 ± 1.0 kg aged 3.0 ± 0.1 years (P>0.05) consisted 3 lactating does of TrC, 3 TrO and 4 TrP.  Milk profiles tested were density, alcohol, pH, and TPC (CFU/ml).  Results showed that density TrO 1.0330±0.0020 was significantly larger compared to density TrP 1.0280±0.0010 and density TrC 1.0280±0.0020 (P<0.05).  In contrast, pH TrO 6.77 ± 0.05 was significantly lower compared to pH TrP 6.95 ± 0.04 and pH TrC 6.86 ± 0.05.  Although TPC TrO 2.334.000±670.400 CFU/ml was significantly larger than TPC TrP or TPC TrC being 14.400±580.600 CFU/ml and 580±670.400 CFU/ml, respectively, (P<0.05).  In summary, milking management by farmers who fed odot silage to their goats were significantly worse indicated by their TPC (P<0.05) though density was significantly higher (P<0.05).    Keywords: database, milk goat, smallholder farms, probiotic and odot silage